Particle swarm optimization algorithm-based PI inverter controller for a grid-connected PV system - Roslan M.F.; Al-Shetwi A.Q.; Hannan M.A.; Ker P.J.; Zuhdi A.W.M. (Public Library of Science, 2023)
Article; controlled study; direct current; electric current; electric potential; electrical parameters; intermethod comparison; inverter; particle swarm optimization; performance; power quality performance; resistor inductor filter; software; total harmonic distortion; transient response time; voltage overshoot; algorithm; electricity; equipment design; power supply; renewable energy; Algorithms; Electric Power Supplies; Electricity; Equipment Design; Renewable Energy